Analysis of fishy taint in duck eggs reveals the causative constituent of the fishy odor and factors affecting the perception ability of this odor. (9th May 2019) - Li, Xingzheng; Huang, Mingyi; Song, Jianlou; Shi, Xuefeng; Chen, Xia; Yang, Fangxi; Pi, Jinsong; Zhang, Hao; Xu, Guiyun; Zheng, Jiangxia
ABSTRACT: Fresh duck eggs normally have an unpleasant fishy odor when compared with eggs from other poultry. However, the cause of this unpleasant smell remains unknown. Besides, we have limited knowledge regarding the perception ability of this odor. Therefore, we aimed to identify the causative substances responsible for the fishy odor in duck eggs, and further evaluate the factors affecting the perception ability of this odor. We detected and quantified the volatile substances in the yolks of Jingjiang duck and Beijing duck eggs using headspace gas chromatography, and evaluated the fishy odor rating scores. We performed association studies on the relationship between the relative content of volatile substances and fishy odor rating scores. The fishy odor of egg yolks from different species/breeds was also characterized. Furthermore, we assessed the species/breeds of poultry eggs and the effects of gender and region of the evaluators on the fishy odor rating score by using an ordinal logistic regression model. Results showed that trimethylamine (TMA ) is responsible for the fishy odor of duck eggs, which was confirmed with subsequent verification ( P < 0.001). The fishy odor of duck eggs was stronger than that of chicken eggs; the fishy odor of Jingjiang duck eggs was the strongest. Results also indicated that the fishy odor perception ability was affected by the gender and region of the evaluators ( P < 0.001). Overall, these data clarified that TMA imparted the fishy odor to duck eggs; factors such as gender and region may affect the fishy odor perception ability.